Autorité de la formation, autorité du formateur : autonomie(s) structurelle, substantielle, individuelle - Camille Roelens (Recherches en Éducation)
This article questions, from the point of view of philosophical politics of education, the issues raised by Le Nouveau monde (Gauchet, 2017) regarding the aims of education and the available means to achieve them. Modern democracies give a triple challenge to those who are born there (part 1) : becoming an individual, becoming autonomous, and stay so whatever the hazards of their life course. Education and formation all along life are then crucial support points. If one admits that authority is a prerequisite for education (as Marie-Claude Blais, Marcel Gauchet and Dominique Ottavi do), then one should also be able to think it at any age, putting it in the context of the new system of individualism which is inherent to the new world (part 2). In other words : how acknowledgment of the authority of educative actors can be considered in a society of individuals ? Symbiotic utterance of authority and kindness can become a precious resource, nevertheless having consequences for the one pursuing this aim.